Electrochemical performances of flexible solid-state fibre supercapacitor based on polypyrrole/ reduced graphene oxide - Abdul Bashid, Hamra Assyaima; Lim, Hong Ngee (2018)
A flexible solid-state fibre supercapacitor was fabricated through a simple electrochemical deposition process of polypyrrole/reduced graphene oxide (PPy/rGO) onto the surface of carbon bundle fibre, using polyvinyl alcohol enriched with potassium hydroxide as a solid-state electrolyte. The surface morphology revealed a high degree of porosity in the PPy/rGO composite; facilitating the ionic penetration, leading to an excellent electrochemical performance. The fabricated supercapacitor recorded a specific capacitance of 96.16 F g-1, with an energy density of 13.35 Wh kg-1 and a power density of 322.85 W kg-1. It showed remarkable pliability at various angles as evidenced by the shape of the cyclic voltammetry curves that remained unchanged. After a series of charging-discharging cycles, the electrochemical performances of the supercapacitor deteriorated due to the changes in the structural properties such as the reduction in pore size, and transformation of the structure of rGO from amorphous to graphitic. In addition, the chemical environment of the electroactive material was disturbed because of the formation of the hydrogen-bridge bond and the redshift of the N-H bending. Consequently, these led to the low diffusion of electrolyte ions, high interfacial resistance, and electronic disorder in the electroactive material because of the collapse of the scaffold, inefficient diffusion of electrolyte ions, and an increase in the electron density that interfered with the electron transfer in the electroactive material.